Pendekatan Neosufisme dalam Pendidikan Agama Islam - Teguh Hadi Wibowo Suprapto; Lukman Hakim; Tobroni; Faridi (Journal of Contemporary Islamic Education, 2024)
Islamic education is a deliberate and planned effort aimed at guiding learners towards the formation of noble personalities, intending to guide their lives towards happiness in both the present world and the afterlife according to Islamic teachings. However, the reality reveals that many learners tend to view Islamic religious education as a subject or course that they must pass to meet minimal graduation requirements, without truly internalizing the values and teachings of Islam for practical application in their daily lives. The aim of this research is to integrate neo-Sufism concepts into the approach of Islamic religious education. This study employs a qualitative approach, utilizing library research methods. The data sources and analysis are drawn from credible scholarly literature. Data validity is verified through content analysis techniques. The result of this research indicate that the neo-Sufism approach to Islamic religious education is an intentional and structured effort directed towards cultivating knowledgeable and morally upright learners. Its primary objective is to enhance the quality of education by not solely focusing on the esoteric dimension of learners but also emphasizing the exoteric dimension and the reconstruction of social ethics. It was implemented by providing gradual spiritual exercises (riyadlah) tailored to the learners' conditions.